2014
DOI: 10.1073/pnas.1312171111
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic droplet vaporization is initiated by superharmonic focusing

Abstract: Acoustically sensitive emulsion droplets composed of a liquid perfluorocarbon have the potential to be a highly efficient system for local drug delivery, embolotherapy, or for tumor imaging. The physical mechanisms underlying the acoustic activation of these phase-change emulsions into a bubbly dispersion, termed acoustic droplet vaporization, have not been well understood. The droplets have a very high activation threshold; its frequency dependence does not comply with homogeneous nucleation theory and locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
159
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 173 publications
(177 citation statements)
references
References 38 publications
13
159
4
1
Order By: Relevance
“…7). This is an entirely different mechanism from the recently proposed focusing effect 175 . Good agreement was found between the modeled size-dependent pressure amplification within the droplet and the measured size dependent vaporization probability.…”
contrasting
confidence: 72%
See 4 more Smart Citations
“…7). This is an entirely different mechanism from the recently proposed focusing effect 175 . Good agreement was found between the modeled size-dependent pressure amplification within the droplet and the measured size dependent vaporization probability.…”
contrasting
confidence: 72%
“…From the pressure profile of the resonant droplet it can also be observed that the amplitude of the pressure at the droplet center exceeds the incident pressure by a factor 2.2. The higher pressure amplification in the center of the droplet results in the largest probability of finding nucleation sites in the center of the droplet, in contrast to the previously developed superharmonic focusing theory 175 .…”
Section: 5contrasting
confidence: 58%
See 3 more Smart Citations